Dengue fever in immunocompromised patients: A systematic review and meta-analysis - Asma Sohail; Shannon Zhong; Phi-Yen Nguyen; Sarah L. McGuinness; Karin Leder (International Journal of Infectious Diseases)
Objectives: Given the complex role of immunity in dengue severity, we aimed to review the clinical course of dengue infection in immunocompromised patients. Methods: We conducted a systematic review of studies reporting outcomes among immunocompromised patients with laboratory-confirmed dengue infection. Meta-analysis using the Mantel-Haenszel method (fixed effects) was performed for studies with control groups. We registered the study with PROSPERO (No. CRD42021258930). Results: We included 115 studies. Among these, 30 studies compared immunocompromised (cases) and nonimmunocompromised (control) patients, focusing mainly on children (n = 22 studies) with malnutrition (n=18). Immunocompromised patients had a higher likelihood of dengue complications (OR 1.87; 95% CI: 1.04-3.35]) but a lower likelihood of severe dengue (OR 0.83; 95% CI: 0.69-1.00]. No significant difference in mortality was observed. In the 85 studies focused solely on immunocompromised patients, severe dengue and mortality rates were 9% and 4%, respectively, mostly among adult solid organ transplant recipients and those with inflammatory diseases. Immunosuppressive treatment alterations and temporary graft dysfunction were reported. Conclusion: Immunocompromised patients have an increased risk of dengue-related complications. However, definitive conclusions about the comparative severity of dengue across different immunocompromised patient groups are limited by a lack of robust data, highlighting the need for well-designed future studies.